Treatment of congenital hypothyroidism in a newborn with malabsorption after subtotal ileum resection. (23rd February 2018) - Schömig, Charlotte S; Robinson, Marie-Ève; von Oettingen, Julia E
Summary: Congenital hypothyroidism requires prompt treatment to prevent adverse health outcomes. Poor intestinal levothyroxine absorption can complicate management. We present a case of a term female newborn with necrotizing enterocolitis (NEC) requiring subtotal ileum resection. Congenital hypothyroidism was diagnosed by newborn screening. Treatment was complicated by intestinal malabsorption of levothyroxine. Intravenous levothyroxine substitution restored euthyroidism and supraphysiologic PO doses subsequently maintained a euthyroid state. After several months, the required levothyroxine dose was weaned down to typical recommended dosing. In conclusion, small bowel resection secondary to NEC may lead to malabsorption of oral levothyroxine. An intravenous levothyroxine dose of approximately 50% typical PO dosing is effective in providing rapid normalization of free T4 and TSH. High PO doses may be required to maintain euthyroidism. Close thyroid function monitoring and immediate therapy adjustment are essential as the individual absorption may vary widely. Normal absorption levels may be regained due to adaption of the neonatal intestines. Learning points: In neonates with malabsorption after ileum resection intravenous levothyroxine replacement should be used to provide normalization of free T4 and TSH. Very high doses of up to 500% usual oral levothyroxine may be required to maintain euthyroidism. The estimated degree of malabsorption can be used to determine the initial dose. Close thyroid function monitoring and immediate therapy adjustment are essential as the absorption and intestinal adaption may vary widely.